Depositional Facies Model and Reservoir Quality of Paleogene Limestone in Labengki Island, Southeast Sulawesi - Mochammad Prahastomi; Achmad Fahruddin; Lauti D.Santy; Ryandi Adlan (Jurnal Geologi dan Sumberdaya Mineral, 2022)
Eastern Indonesia has become an attractive venture for hydrocarbon exploration since 10 years ago. The discovery of hydrocarbon from Miocene carbonate of Tondo Formation has opened a new opportunity and hopes in the Southeast Sulawesi region. Can we find other potential reservoirs in Southeast Sulawesi? In this study, we assess and reconstruct the depositional model and the reservoir quality of the Paleogene Tampakura Formation in Labengki Island, Southeast Sulawesi. This field observation and petrographical study revealed that: (1) Tampakura Formation comprises mainly of grainstone, boundstone and floatstone with minor packstone and dolomitic wackestone/mudstone, (2) Tampakura Formation was deposited mainly in wide carbonate sand shoals and reef margin belt of rimmed carbonate shelf, (3) Boundstone and floatstone facies could be the best reservoir candidate in the region since they show extensive porosities development of cavernous and fracture porosity, (4) Dolomite cementation has deteriorated the reservoir quality of packstone which was deposited in platform interior-restricted marine, (5) Extensive calcite cementation in grainstone facies has reduced the reservoir quality of Tampakura Formation. However, locally, solution enlarged fracture porosity may have enhanced it. We suggest that post collision event of Late Oligocene - Early Miocene between Australian-originated microcontinent and ophiolite complex was highly responsible to create cavernous porosity. The collision resulted in the folding and uplifting of Tampakura Formation to the subaerial exposure. The carbonate strata were exposed to the surface developing a cavernous porosity and potentially becoming the best reservoir candidate for the next exploration target.Keywords: Carbonate facies, Kendari Basin, reservoir quality, Tampakura Formation.